PERANCANGAN MOBILE WEBSITE CLOUD KITCHEN LAA ZURU MENGGUNAKAN METODE DESIGN THINKING - Paramitha, Vanya Amabella Marsha; Martini, Sri; Mufidah, Ilma (Universitas Bina Taruna Gorontalo, 2023)
The aim of this research is to produce a U/UX prototype for a cake ordering website using a design thinking approach. Design thinking is a method for developing business innovations that focus on users. Two phases are involved: the inspiration and ideation phases. Data collection through observation and in-depth interviews, the inspiration phase understands user needs and goals. The ideation stage involves brainstorming with stakeholders and selecting ideas into solutions, in the form of features for the Laa Zuru mobile website. The resulting website prototype was tested through the System Usability Scaling questionnaire. The test results show a score of 82.5, indicating the usability of the mobile website prototype is in category B (Acceptable) and has an adjective rating of